TARIAN SPIRITUAL JALALUDDIN RUMI - Eni Murdiati (Wardah, 2011)
The Whirling Dervishes (The Darwisy the Round and round) or Sama’. The term used by the Maulawiyah or Jalaliyah adherents of this, by doing a dance around in circles, accompanied by drums and flute, in the devotions they are to reach ecstasy. Rumi and the legendary spiritual dance into a work of great almighty to fill in a drought spitual man approached the Creator.